Atrial GIRK Channels Mediate the Effects of Vagus Nerve Stimulation on Heart Rate Dynamics and Arrhythmogenesis - Lee, Steven W.; Anderson, Allison; Guzman, Pilar A.; Nakano, Atsushi; Tolkacheva, Elena G.; Wickman, Kevin (Frontiers in Physiology, 2018)
Diminished parasympathetic influence is central to the pathogenesis of cardiovascular diseases, including heart failure and hypertension. Stimulation of the vagus nerve has shown promise in treating cardiovascular disease, prompting renewed interest in understanding the signaling pathway(s) that mediate the vagal influence on cardiac physiology. Here, we evaluated the contribution of G protein-gated inwardly rectifying K+ (GIRK/Kir3) channels to the effect of vagus nerve stimulation on heart rate, heart rate variability, and arrhythmogenesis in anesthetized mice. As parasympathetic fibers innervate both atria and ventricle, and GIRK channels contribute to the cholinergic impact on atrial and ventricular myocytes, we collected in vivo electrocardiogram recordings from mice lacking either atrial or ventricular GIRK channels, during vagus nerve stimulation. Vagus nerve stimulation decreased heart rate and increased heart rate variability in control mice, in a muscarinic receptor-dependent manner. This effect was preserved in mice lacking ventricular GIRK channels, but was nearly completely absent in mice lacking GIRK channels in the atria. In addition, atrial-specific ablation of GIRK channels conferred resistance to arrhythmic episodes induced by vagus nerve stimulation. These data indicate that atrial GIRK channels are the primary mediators of the impact of vagus nerve stimulation on heart rate, heart rate variability, and arrhythmogenesis in the anesthetized mouse.